The creative economy for sustainable tourism in the post-mining era in Pangkalpinang city - Shelia, Windy; Estresia, Fitria Gusti; Irawan, Wawan (Indonesian Tourism Journal, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Pangkalpinang are crucial contributors to the local economy, especially in the post-tin mining era, by driving economic diversification and regional development. This research delves into the role of the creative economy in fostering sustainable tourism during this transitional period. Through a qualitative approach, the study employs the SWOT analysis framework to assess the development of MSMEs and their connection to sustainable tourism in Pangkalpinang. The strengths of these MSMEs are evident in their distinctive product offerings, robust stakeholder networks, and the recognition and certifications they have attained. These elements position them well within the market. However, they face notable internal challenges, including limited resources, technological constraints, and financial difficulties, which hinder their growth potential. Externally, MSMEs in Pangkalpinang contend with high economic inflation, stiff competition from larger retail entities, and shifting consumer preferences driven by economic downturns. These factors create a challenging environment for MSMEs to thrive. Despite these challenges, there are significant opportunities for growth. MSMEs can capitalize on product diversification, which allows them to cater to a broader range of consumer needs. Additionally, there is substantial support from the government and various institutions, which can provide the necessary backing for these enterprises. Aligning their business models with sustainable tourism trends also presents a promising avenue for long-term success. By leveraging these opportunities, MSMEs in Pangkalpinang can enhance their resilience and contribute meaningfully to sustainable regional development in the post-mining era.